Bridging the Gender Gap in Turkish Politics: The actors promoting female representation - Bilgili, Nazlı Çağın (My University, 2011)
Gender gap is still persistent in Turkey in diff erent areas despite the fact that policies and measures pertaining to gender equality have been improved in the past couple of years. Believing in the prominence of gender gap in politics due to the authority of decision-making that belongs to the political fi gures, this article focuses on the increase –although slow- in female representation in the Turkish Parliament with a special focus on the last two general elections that were held under the infl uence of massive campaigns by women’s organizations. The last general elections held on June 12, 2011 marked an approximately 60% increase in the number of women parliamentarians which rose from 48 to 78. The article argues that three actors –civic actors, international actors namely the EU and the representatives of the Kurdish movement- have been infl uential in this increase by raising media and public attention on the topic. The campaigns that attracted great attention in the media, the emphasis of the EU progress reports on gender equality and the 40% gender quota applied among the Kurdish parliamentarians are some of the topics discussed with regard to their infl uence on the recent increase in female representation in Turkey.
Keywords: Women's underrepresentation; political gender gap; civic attempts; gender quota; gender equality